The effects of non-nutritive sweeteners on energy and macronutrients intake in adults: a grade-assessed systematic review and meta-analyses of randomized controlled trials - Kimia Rostampour; Kimia Rostampour; Kimia Rostampour; Fatemeh Moghtaderi; Fatemeh Moghtaderi; Fatemeh Moghtaderi; AmirHossein Najafi; AmirHossein Najafi; AmirHossein Najafi; Behnaz Seyedjafari; Behnaz Seyedjafari; Behnaz Seyedjafari; et al. (Frontiers in Nutrition)
ObjectivesThe effect of non-nutritive sweeteners (NNSs) on long-term satiety is not well understood. This systematic review and meta-analysis were performed to investigate the effect of NNSs on long-term total energy and macronutrients intake.MethodsOnline databases including Scopus, PubMed, ISI Web of Science, and Google Scholar were searched up to September 2024 to find relevant randomized control trials (RCTs). A random effects model was used for estimating the overall effects.ResultsThe results showed a reducing effect of NNSs consumption vs. sugar on total energy intake [total energy intake change = −175.26 kcal/day, 95% confidence interval (CI): −296.47 to −54.06, I2 = 61.19%] and carbohydrate intake [Hedges’ g = −0.35, 95% CI: −0.63 to −0.06, I2 = 58.99%]. While, NNSs intake vs. water was not associated with significant change in total energy intake [total energy intake change = 29.94 kcal/day, 95% CI: −70.37 to 130.24, I2 = 34.98%] and carbohydrate intake [Hedges’ g = 0.28, 95% CI: −0.02 to 0.58, I2 = 65.26%]. The Consumption of NNSs compared to the either sugar or water did not have a significant effect on fat intake [Hedges’ g sugar = 0.08, 95% CI: −0.10 to 0.26, I2 = 8.73%/ fat intake change water = 0.20 g/day, 95% CI: −3.48 to 3.88, I2 = 0%] and Protein intake [Hedges’ g sugar = 0.16, 95% CI: −0.11 to 0.42, I2 = 50.83%/Hedges’ g water = 0.00, 95% CI: −0.15 to 0.16, I2 = 0%].ConclusionIn summary, our findings suggest that NNSs consumption may be effective in reducing total energy and carbohydrate intake compared to sugar.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=432816, CRD42023432816.